Tradução cultural em O último suspiro do mouro de Salman Rushdie e Relato de um certo Oriente de Milton Hatoum - Adolfo, Gabriel Gustavo (2017)
This study intends to analyse how social interactions, often marked by hybridity and cultural translation, are represented in the plots of the novels The moor’s last sigh (1995, O último suspiro do mouro, 1996) by Salman Rushdie and Relato de um certo oriente (1989, Tale of a Certain Orient, 2008) by Milton Hatoum. The analysis will focus on the narrator ’s perspective and will try to show how the elements of the two narratives contribute to the literary concept of such novels. The conceptual framework is drawn from the perspective of cultural studies and post-colonial literary criticism, including considerations on diaspora, discursive manifestations derived from the encounter between distinct cultures and comparative literature, among others. This work is based on concepts postulated by theorists such as Edward Said, Homi Bhabha, Franz Fanon, Gayatry C. Spivak, Stuart Hall, Mikhail M. Bakhtin, Walter Benjamin, Silviano Santiago and Antonio Candido. The analysis of the two novels also seeks to demonstrate how literature can challenge traditional kinds of knowledge and discourses of ethnic-cultural "purity" and national identity